The last midwife - Dallas, Sandra (St. Martin's Press, 2015)
"It is 1880 and Gracy Brookens is the only midwife in a small Colorado mining town where she has delivered hundreds, maybe thousands, of babies in her lifetime. She is a gifted and important resource for the women of her hardscrabble community, a position earned through wisdom and trust. Most women in Swandyke couldn't even imagine getting through their pregnancy and labor without Gracy by their sides. But everything changes when a baby is found dead...and the evidence points to Gracy as the killer. Gracy knows she didn't commit the crime. But her innocence isn't quite that simple, either. She knows things and that's dangerous."--